RARE-23. HIGH DOSE METHOTREXATE WITH OR WITHOUT VINCRISTINE FOR PRIMARY CNS LYMPHOMA, THE OHIO STATE UNIVERSITY EXPERIENCE. (11th November 2019) - Freeman, Tracelyn; Legasto, Carlo; Schickli, Alex; McLaughlin, Eric; Giglio, Pierre; Puduvalli, Vinay; Gonzalez, Javier
Abstract: OBJECTIVES: 1) Determine the response rate (RR) after chemotherapy with high-dose methotrexate with or without vincristine in patients with primary CNS lymphoma. 2) Determine the difference in adverse effects with the use of vincristine. 3) Determine the difference in progression-free survival (PFS) and overall survival (OS) between the 2 groups. METHODS: Retrospective study in patients 18–89 years with primary CNS lymphoma that received chemotherapy with rituximab (R), methotrexate (M), procarbazine (P), and vincristine (V) R-MPV, R-MV, R-MP, or R-M between 2010 and 2018 at The Ohio State University. Response rate by cycle 7 was compared with odds ratio. Kaplan-Meier curves were used to compare OS and PFS. RESULTS: 29 patients were included: 16 (55%) received vincristine. 14/16 patients treated with vincristine and 4/13 in the other group also had procarbazine. 12/29 patients had a complete response after a maximum of 7 cycles. The odds of complete response were 24% higher in patients treated with vincristine but the difference did not reach statistical significance. Side effects were higher in the vincristine arm. The most common was peripheral neuropathy (75% vs 8% - all grades). Median PFS was 60.7 months for the vincristine group and 23.7 months for the non-vincristine group. Median OS was 85.3 months for the vincristine group and 67.1 months for the non-vincristine group. OS and PFS curves did not differ significantly. CONCLUSIONS: The use of vincristine in high-dose methotrexate chemotherapy regimens for CNS lymphoma was not associated with a statistically significant difference in RR. Patients who received vincristine had more side effects and there were no significant differences in OS and PFS. The sample size and rate of procarbazine use may be confounding factors. Further studies are necessary to determine the effect of vincristine in RR and OS in these patients.